Analysis of Non-Performing Loans (NPL) at BRI Bank Tbk in 2010-2022 - Darwita Arini Nasution; Enjelina Sinaga; Gabriella Dominggoes Panjaitan; Histi Trifesi Naibaho (PT FORMOSA CENDEKIA GLOBAL, 2023)
Non-Performing Loans (NPL) are an important indicator in assessing asset quality and credit risk management within financial institutions. This study aims to determine the main non-performing loan (NPL) at PT. Bank Rakyat Indonesia BRI Tbk. This research uses qualitative methods. The data obtained is secondary data with quantitative data types. The research instrument used in collecting data is the financial statements of PT. Bank BRI Tbk in the form of a financial ratio report for 2010–2022. The results of this study showed that the lowest NPL ratio level in 2013 was 1.63% and the highest NPL ratio level in 2021 was 3.00%. The average NPL during 2010–2022 was 2.34%, which is included in the healthy category.